Mangiferin Attenuates LPS/D-GalN-Induced Acute Liver Injury by Promoting HO-1 in Kupffer Cells - Yang, Sen; Kuang, Ge; Zhang, Liangke; Wu, Shengwang; Zhao, Zizuo; Wang, Bin; Yin, Xinru; Gong, Xia; Wan, Jingyuan (Frontiers in Immunology, 2020)
Acute liver injury and its terminal phase, hepatic failure, trigger a series of complications, including hepatic encephalopathy, systematic inflammatory response syndrome, and multiorgan failure, with relatively high morbidity and mortality. Liver transplantation is the ultimate intervention, but the shortage of donor organs has limited clinical success. Mangiferin (MF), a xanthone glucoside, has been reported to exert excellent anti-inflammatory efficacy. Here, a lipopolysaccharide (LPS)/D-galactosamine (D-GalN)-induced acute liver injury mouse model was established to investigate the protective role of MF and the underlying mechanisms of action. Pretreatment with MF improved survival, abated serum aminotransferase activities, and inhibited hepatic TNF-α production in LPS/D-GalN-challenged mice. Through Kupffer cell (KC) deletion by GdCl3 and KC adoptive transfer, KCs were confirmed to be involved in these beneficial effects of MF. MF reduced LPS-mediated TNF-α production via the suppression of the TLR4/NF-κB signaling pathway in vitro. MF promoted HO-1 expression, but the knockdown of HO-1 prevented TNF-α inhibition, suggesting that the damage-resistance effects of HO-1 occurred via the suppression of TNF-α synthesis. When HO-1-silenced KCs were transferred to the liver with KC deletion, the protective effect of MF against LPS/D-GalN-induced acute liver injury was reduced, illustrating the role of KC-derived HO-1 in the anti-injury effects of MF. Collectively, MF attenuated acute liver injury induced by LPS/D-GalN via the inhibition of TNF-α production by promoting KCs to upregulate HO-1 expression.